2012
DOI: 10.4161/onci.20897
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell exosomes directly kill tumor cells and activate natural killer cells via TNF superfamily ligands

Abstract: Autocrine and paracrine cell communication can be conveyed by multiple mediators, including membrane-associate proteins, secreted proteins and exosomes. Exosomes are 30–100 nm endosome-derived vesicles consisting in cytosolic material surrounded by a lipid bilayer containing transmembrane proteins. We have previously shown that dendritic cells (DCs) express on their surface multiple TNF superfamily ligands (TNFSFLs), by which they can induce the apoptotic demise of tumor cells as well as the activation of natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(211 citation statements)
references
References 31 publications
5
204
1
1
Order By: Relevance
“…We found an elevated expression of TNF‐α in mature DC‐exos and they were mainly expressed on exosomal membrane. This finding was consistent with previous studies 8, 24. We then down‐regulated TNF‐α in DC‐exos and observed that the expression of adhesion molecules by HUVECs were attenuated, indicating a direct interaction between DC‐exos and HUVECs by TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found an elevated expression of TNF‐α in mature DC‐exos and they were mainly expressed on exosomal membrane. This finding was consistent with previous studies 8, 24. We then down‐regulated TNF‐α in DC‐exos and observed that the expression of adhesion molecules by HUVECs were attenuated, indicating a direct interaction between DC‐exos and HUVECs by TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
“…If a protein is mainly located on the membrane, then the intact concentration should be as similar as the lysed concentration. Otherwise, the lysed concentration should be significantly higher than the intact concentration 8. Using this method, we found that TNF‐α was mainly expressed on the exosomal membrane and mature DC‐exos, compared with immature DC‐exos, displayed a higher expression of TNF‐α (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…To test the potential for exosomes to be used as cell-free vaccines against cancers, DC-derived exosomes have undergone phase I trial and are currently in phase II trial [12,103105]. In addition to MHC-bound antigens expressed on the exosomal surface, mature DC-derived exosomes also show surface expression of ICAM-1, which is important for the induction of immune responses, such as T-cell activation [106], and the NKG2D ligand, which is a TNF superfamily ligand that binds directly to NK cells to induce their activation/proliferation and cause an anti-tumour immune response [107,108]. …”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…miRNA, mRNA), integrins (type of integrin can be cell-type specific), lysobisphosphatidic acid (LBPA), cholesterol, ganglioside GM3 [29,30]. Cell type specific: MHC-II, CD80, CD86 and complement shielding proteins CD55/59 (in DC) [31], tumor-associated antigens (TAA; e.g. GP100 in melanoma cells) [32], perforin (in natural killer T cells) [33].…”
Section: Biogenesis Cargo Loading and Compositionmentioning
confidence: 99%